Pelatihan Penggunaan Aplikasi Pengukur Kecerdasan di Sekolah Dasar - Alberth Supriyanto Manurung; Abdul Halim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of digital technology provides opportunities for elementary schools to improve the quality of student assessments through the use of intelligence-measuring applications. However, observations at SDN Setia Asih 01, Bekasi Regency, showed that most teachers lack the knowledge and skills to use these applications to support the identification of student learning potential. This community service activity aims to improve teachers' competence in utilizing intelligence-measuring applications so that they can support the initial assessment process and develop learning that is more appropriate to student characteristics. The implementation method uses a Participatory Learning and Action approach, which includes needs analysis, material development, training, application practice, mentoring, and activity evaluation. Evaluation was conducted through observation, discussion, and questionnaires to determine the level of understanding and skills of participants after participating in the training. The results of the activity showed that teachers showed high enthusiasm during the training and were able to operate the intelligence-measuring application independently, starting from the registration process, data entry, assessment implementation, and interpretation of measurement results. In addition, participants gained an understanding of how to use assessment results as a basis for designing more adaptive and student-centered learning. The mentoring provided also helped participants overcome technical obstacles during the application practice. This program is expected to be the first step in developing a sustainable technology-based learning culture to improve the quality of educational services in elementary schools.